Applicant-to-Residency Program Communication: Does It Matter?. (November 2020) - Solis, Roberto N.; Quesada, Pompeyo R.; Ma, Cheng; Olinde, Lindsay M.; Diaz, Rodney C.
Objectives: To elucidate the frequency and types of pre- and post-interview communication that applicants engage with programs, to garner the perceptions of both applicants and program directors (PDs), and determine if communication influences outcomes. Subjects and Methods: Electronic surveys were distributed to otolaryngology residency applicants, and to PDs of ACGME-accredited otolaryngology programs after the 2018 to 2019 application cycle. Results: 93 of 324 applicants (28.7%) and 33 of 106 PDs (31.3%) responded. In the pre-interview period, 58.1% of applicants sent emails of interest, and 41.9% had a mentor initiate communication. In the post-interview period, the majority of applicants (82.8%) sent notes of intent to their number one choice, and 32.3% had a faculty mentor communicate this on their behalf. The majority of PDs (84.8%) were undecided or did not believe that emails of interest influence decisions to offer an interview, whereas 81.8% believed that communication initiated by an applicant's mentor has an impact on interview offers. No PD agreed that declarations of intent from applicants have an impact on their rank lists, while only 33.3% of PDs believed that a mentor communicating this for an applicant has some impact. Our statistical findings are in agreement with these perceptions as neither applicant-initiated pre-interview ( P = .54), mentor-initiated pre-interview ( P = .62), applicant-initiated post-interview ( P = .11) nor mentor-initiated post-interview ( P = .78) communications influenced the number of interviews received or ultimate match outcome. Conclusion: Pre- and post-interview communication practices vary widely among otolaryngology applicants. Applicant-initiated communication has no impact on outcomes, while mentor-initiated communication is perceived to have more benefit, despite not impacting interview or match outcomes in this study.